Pelatihan Jurnalistik Untuk Warga Desa Liwulangang dalam Merekam Peristiwa di Desa - Charles De Albert Tamelab; Mikhael Rajamuda Bataona (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The digital media era is marked by a major shift in how information is accessed, produced, and disseminated. The internet and electronic devices such as smartphones enable anyone to become an information producer through social media, blogs, and other digital platforms. Media is no longer dominated by large institutions but also by ordinary individuals, creating a more democratic communication space. Digital communication enables the two-way exchange of messages in the form of text, images, audio, and video, accelerating the dissemination of information and strengthening collaboration across distances. However, challenges such as the spread of hoaxes and the ethical use of digital media still require attention. One form of active community participation is citizen journalism, where individuals cover and share local issues through digital media. This was evident in the OMK Week activities at Liwulagang Parish, which were documented by the OMK team through photos and videos. This documentation aims to preserve archives, serve as material for reflection, and expand publications to the congregation through social media, especially Facebook. The content shared emphasizes the spirituality, solidarity, and creativity of OMK, while also motivating the younger generation to become active in church life. To support citizens' ability to utilize digital media appropriately, journalism training was conducted to increase public understanding of the wise use of social media. The research methods used in this activity included data collection, outreach, and interviews, with results demonstrating the importance of open communication, feedback between presenters and participants, and active community participation.